Страхування відповідальності перевізника - Nykyforak, Volodymyr; Никифорак, Володимир Михайлович (Чернівецький національний університет. Видавництво "Рута"., 2001)
In the article the features of rise, development and functioning of the basic kinds of civil liability insurance of the carriers are opened: liability insurance of the air carriers, liability insurance of the marine carriers, liability insurance of the auto carriers.
Keywords: перевізник; договір страхування цивільно-правової відповідальності; відповідальність; страхування відповідальності перевізника